PERAN BIOPSI HEPAR DALAM MENEGAKKAN DIAGNOSIS IKTERUS OBSTRUKTIF EKSTRA HEPATIK - Sherly M, Yuliana; Widita, Haris; Ardita, IG; Soemohardjo, Soewignjo (journal of internal medicine, 2012)
Obstructive icterus is caused by 2 major group from the intrahepatic and ekstrahepatic and ekstrahepatic. Generally to confirm clinical diagnosis is done with USG imaging. In which USG easily could differentite the cause of the bile duct (accuracy 90%). The mothode of biopsy is only to evaluate the intrahepatic icterus. In certain cases, it is not easy to confirm either its obstructive icterus extraheaptic or intrahepatic, as the bile duct smetimes to seen clearly on the USG examination, which is to assure the side of obstructive because the distal part of the bile duct difficult to be seen in 30%-50% cases until hepatic biopsy is reduced. Meanwhile the histopatology appearance of extrahepatic icterus are marked by classis changes known as ductuler reaction, which as the oedema of connective tissue, ductular proliferation and neutrofil infiltration. There by here, we report the case of a man, 53 years old with obstructive icterus, where in the beginning is suspected as intrahepatic cholestasis and the cause of extrahepatic icterus is unknown, then the diagnosis was confirmed with histopatology examination.
Keywords: extrahepatic icterus, liver biopsy